PENGARUH SCARCITY MESSAGE DAN DISCOUNT TERHADAP IMPULSE BUYING PADA FOLLOWERS AKUN TWITTER SHOPEE INDONESIA - Kholiq, Jabar; Fadilla, Arif (Jurnal Ilmiah Wahana Pendidikan, 2024)
This research was conducted to obtain empirical evidence, explain the phenomenon, and make conclusions about the effect of the Scarcity Message and Discount variables on Impulse Buying on Followers of the Shopee Indonesia Twitter Account. This study was conducted using descriptive and verification methods, namely knowing, explaining and analyzing. In this study, a sample of 384 where respondents were selected using purposive sampling. The research variables include the independent variables namely Scarcity Message (X1) and Discount (X2), as well as the variable Impulse Buying as the dependent variable. The data analysis technique uses the Likert scale technique and path analysis using the Succesive Interval Method (MSI) tool, the Microsoft Excel 2019 computer program and SPSS version 23, The results of this study prove that there is a correlation between Scarcity Message and Discount and has a relationship with low and unidirectional criteria. The results of hypothesis testing partially, the Scarcity Message variable and the Discount variable have a significant effect on the Impulse Buying variable. There is a simultaneous effect of Scarcity Messages and Discounts on Impulse Buying on Followers of the Shopee Indonesia Twitter Account.